The Effectiveness of Health Education on Premenstrual Syndrome toward Knowledge and Attitudes of Adolescent Girls at LKSA Panti Asuhan Aisyiyah Kudus - Nafi'ah Khumairatun Az-Zahra; Noor Hidayah; Sukesih Sukesih (Sean Institute, 2026)
Premenstrual syndrome (PMS) is a reproductive health problem commonly experienced by adolescent girls and can cause physical and emotional disturbances that affect daily activities and quality of life. Limited knowledge and inappropriate attitudes toward PMS are still frequently found, particularly among adolescent girls living in orphanages who have restricted access to health information. This study aimed to determine the effectiveness of health education on premenstrual syndrome in improving knowledge and attitudes of adolescent girls at LKSA Aisyiyah Kudus Orphanage. This study employed a quantitative approach with a pre-experimental one-group pretest–posttest design. The study population consisted of all adolescent girls at LKSA Aisyiyah Kudus Orphanage, totaling 34 respondents, with total sampling used as the sampling technique. Data were collected using knowledge and attitude questionnaires administered before and after the health education intervention, which was delivered through PowerPoint (PPT) media using an experience sharing technique. Data analysis was conducted using univariate and bivariate analyses, and the Wilcoxon Signed Rank Test was applied. The results showed a significant improvement in both knowledge and attitudes of adolescent girls after the health education intervention (p < 0.05), indicating a meaningful difference between pretest and posttest measurements. These findings demonstrate that health education is effective in increasing knowledge and fostering positive attitudes among adolescent girls toward premenstrual syndrome.